Memberdayakan Ayah Indonesia: Dampak Edukasi Laktasi secara Daring Terhadap Literasi Kesehatan dan Breastfeeding Self-Efficacy - Hidayat, Agus Rahmat; Handayani, Sarah; Pramudho, PA Kodrat; Nuryati, Tati; Putri Deli, Aragar (Fakultas Kedokteran Universitas Trisakti, 2023)
Background Breastfeeding is vital for the health of both mothers and infants. However, only 51.5% of infants under six months are exclusively breastfed in Indonesia. Research has consistently demonstrated the positive impact of engaging fathers in breastfeeding programs, leading to improved breastfeeding outcomes. However, lactation education activities for fathers in Indonesia are limited. By measuring the impact of the intervention on fathers' health literacy and self-efficacy, this research aims to contribute to enhancing breastfeeding practices and support in Indonesia. Methods This quasi-experimental study aimed to evaluate the impact of online lactation classes on breastfeeding health literacy and fathers' self-efficacy. Participants (N=35) were randomly assigned to the treatment or control group, and pre-and post-tests were conducted. The intervention group received two-day online lactation education via Zoom, while the control group received a breastfeeding e-poster on WhatsApp. Data analysis involved univariate analysis for variable characterization and bivariate analysis using statistical tests such as Paired Sample T-Test, Wilcoxon, and Mann-Whitney tests, with a significance level of p<0.05. Results The study's findings demonstrate the efficacy of the online lactation classes in the intervention group compared to the control group, as evidenced by significant improvements in fathers' health literacy (p=0.035) and self-efficacy (p=0.005) in supporting exclusive breastfeeding by their wives. Conclusions The research found that online breastfeeding classes for fathers positively affect their health literacy and self-efficacy in supporting breastfeeding. This approach was more effective than electronic posters via a WhatsApp group in increasing health literacy, but the signs positively affected fathers' self-confidence.